2021
DOI: 10.1007/s00402-021-03801-7
|View full text |Cite
|
Sign up to set email alerts
|

Standard radiographic assessments of distal radius fractures miss involvement of the distal radioulnar joint: a diagnostic study

Abstract: Introduction Distal radius fractures account for one-fifth of all fractures in the emergency department. Their classification based on standard radiographs is common practice although low inter-observer reliabilities and superiority of computer tomography (CT) scanning in evaluation of joint congruency have been reported. Materials and methods We retrospectively analyzed 96 displaced distal radius fractures scheduled for open reduction and internal fixatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The presented PSI method had one case 14% (1/7) with a postoperative step-off over 1 mm and no cases above 2 mm. The additional accuracy of joint reconstruction achieved using PSI seems to have no influence on the functional outcome according to the literature [5,6,25,26]. Further long-term follow-up will answer the question concerning the development of further postraumatic degeneration.…”
Section: Discussionmentioning
confidence: 90%
“…The presented PSI method had one case 14% (1/7) with a postoperative step-off over 1 mm and no cases above 2 mm. The additional accuracy of joint reconstruction achieved using PSI seems to have no influence on the functional outcome according to the literature [5,6,25,26]. Further long-term follow-up will answer the question concerning the development of further postraumatic degeneration.…”
Section: Discussionmentioning
confidence: 90%
“…We review them closely with repeat radiographs at 1 week, 2 weeks, and 6 weeks. We do not routinely use CT scan to assess alignment of two-part fractures unless concerned about involvement of the sigmoid notch or alignment at the distal radioulnar joint (DRUJ) as we are aware that standard radiographic assessments of distal radius fractures are not sufficient to accurately determine the involvement of the DRUJ 20 Due to the limitations described above, further research is indicated and a prospective cohort study with patient reported outcome measures would be useful to reinforce the validity of this measurement.…”
Section: Discussionmentioning
confidence: 99%
“…However, computed tomography scans allow for a better assessment of fracture complexion and extensions into articular surfaces. 31 Finally, it would have also been convenient for a longer follow-up period to better assess the appearance of complications related to the volar plate or suspension system.…”
Section: Discussionmentioning
confidence: 99%